2018
DOI: 10.3855/jidc.10122
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and non-opportunistic character of Blastocystis spp.: a hospital-based survey in Central Cameroon

Abstract: Introduction: Blastocystis spp. is a protist found in humans. Although usually the most frequent protozoa found in stool samples of both symptomatic and healthy subjects, its pathogenic or rather opportunistic role is yet to be clearly elucidated. To attempt to fill this gap, a cross-sectional study was conducted to compare the frequency of Blastocystis spp. in HIV positive (HIV+) versus HIV negative (HIV-) individuals in four health facilities of the Center Region of Cameroon. Methodology: Stool samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The reasons, we argued, were that the children under the age of 3 years have weak immune systems and are rarely prescribed a vermifuge. Conversely, no significant difference was found between the two groups with respect to sex (p > .05), similar to results reported in other studies (AbuOdeh, Ezzedine, Samie, Stensvold, & ElBakri, 2016;Jupsa-Mbiandou et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The reasons, we argued, were that the children under the age of 3 years have weak immune systems and are rarely prescribed a vermifuge. Conversely, no significant difference was found between the two groups with respect to sex (p > .05), similar to results reported in other studies (AbuOdeh, Ezzedine, Samie, Stensvold, & ElBakri, 2016;Jupsa-Mbiandou et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that the prevalence of the parasite is higher in those with mental retardation, which can be due to the lack of sanitary considerations among this group, with more pronounced symptoms in patients with the immune system deficiency (10,14,63,64). This indicates that the parasite is opportunistic; however, this claim has been rejected by some other studies (65,66). In a study conducted on mice, it was shown that younger mice were more susceptible to infections with Blastocystis spp.…”
Section: Host Indicesmentioning
confidence: 98%